Innovation Process Management as the Basis of Enterprise Development - Kurmanov, Nurlan; Dogalov, Amangeldy; Toktasynov, Sungat; Baktymbet, Assem; Baktymbet, Saule; Rakhimbekova, Assel; Satbayeva, Aizhan (International Review of Management and Marketing, 2017)
The purpose of this study is to examine the peculiarities and development of practical recommendations for the further improvement of management mechanisms of innovative processes in Kazakhstan. The utilized methodology: a systematic approach, comparison, a scientific abstraction, collection, analysis and synthesis of information, expertise and statistical methods. The main value of the work: the theoretical justification of the support system of activities of Kazakhstani enterprises by promoting innovative activities and development of knowledge-consumptive technologies. Keywords: knowledge-consumptive technologies, commercialization of technologies, the demand for innovation, innovation process management. JEL Classifications: M 13, O 32